Tren Penelitian Integrasi Budaya Lokal Indonesia dalam Pembelajaran di Sekolah (2022 – 2026): Analisis Bibliometrik - Hafida Rahma; Nisrina Azizah; Eko Handoyo (Journal of Literature Review, 2026)
This study aims to analyze research trends on the integration of local culture in school learning during the 2022–2026 period using a bibliometric approach with data sourced from the Scopus database through the keywords "learning," "culture," and "primary education," yielding 15 selected articles. The analysis reveals a significant increase in publications, particularly in 2025–2026, with a dominant contribution from Indonesia. Three main findings were identified: (1) research trends have shifted from cultural preservation toward the utilization of local culture as a source of learning innovation, character education, and 21st-century competency development; (2) the integration of local culture is realized through five forms, namely the development of teaching materials, the use of digital media, the application of innovative learning models, curriculum design and school culture, and extracurricular activities; and (3) the challenges encountered are multidimensional, encompassing limited culture-based learning resources, digital literacy gaps, the complexity of technology integration, and globalization pressures on cultural sovereignty. In conclusion, local culture has evolved from a supplementary element into a pedagogical foundation that serves pedagogical, cultural, and transformational functions in learning.